Fusion Proteins Containing Family 1 and Family 2 PspA Fragments Elicit Protection against Streptococcus pneumoniae That Correlates with Antibody-Mediated Enhancement of Complement Deposition - Darrieux, M. (American Society for Microbiology (ASM), 2007)
PspA is an important pneumococcal vaccine candidate that is capable of inducing protection in different animal models. Because of its structural diversity, a PspA-based vaccine should contain at least one fragment from each of the two major families (1 and 2) in order to elicit broader protection. In the present work, we have tested the potential of PspA hybrids containing fused portions of family 1 and 2 (PspA1ABC-4B and PspA1ABC-3AB) PspA fragments to induce protection against pneumococci bearing distinct PspA fragments. Sera from mice immunized with these hybrid PspA fragments were able to increase C3 deposition on pneumococci bearing PspA fragments from both families, in contrast with sera made against the PspA family 1 (PspA1ABC) and PspA family 2 (PspA3ABC) fragments, which were effective only within the same family. Although PspA hybrids were able to extend protection against pneumococcal infection with strains bearing diverse PspA fragments, the immunity elicited by family 2 was clade dependent, suggesting that PspA fragments from family 2 clades 3 and 4 should both be included in a comprehensive PspA vaccine. These results indicate that PspA fusion proteins constitute an efficient immunization strategy for future PspA-based antipneumococcal vaccines since they are able to extend protection provided by a protein derived from a single transcript.